The mediating role of meaning in work in promoting teachers’ technology integration - Pambudi, Dholina Inang; Suyatno, Suyatno; Wantini, Wantini; Patimah, Lilis; Mardati, Asih; Nurfirdaus, Nunu (Frontiers in Education, 2024)
Teachers' technology integration is an essential aspect that has garnered significant attention from both teachers and several studies over the past three decades. This focus has been further reinforced by the COVID-19 pandemic, where the aspect has become a determining factor in the success of the teaching and learning process in classrooms. Previous results showed that there were limited studies linking the variable of teachers' technology integration with meaning in work as an internal variable. Therefore, this study aimed to develop a conceptual model on the role of meaning in work in mediating the relationship of digital leadership and self-efficacy with teachers' technology integration using the analysis of AMOS-structural equation modeling (SEM). Respondents consisted of 200 Junior High School teachers in East Kalimantan Province, an area in the eastern part of Indonesia, projected to be the new capital. A total of four variables were examined in this study, including meaning in work, digital leadership and self-efficacy, and teachers' technology integration as variables Z, X, and Y, respectively. The results showed that: 1) digital leadership affected meaning in work and teachers' technology integration, 2) self-efficacy affected meaning in work and teachers' technology integration, 3) meaning in work affected teachers' technology integration, and 4) meaning in work could mediate the relationship between digital leadership and self-efficacy in teachers' technology integration. These findings were expected to 1) provide a deeper understanding of the association between digital leadership, self-efficacy, and meaning in work as well as their effect on teachers' technology integration. A proper understanding of the essential role of meaning in work as a potential mediator in these relationships was also provided. Therefore, the results provided a strong